One Possible Mechanism of Pulsed Dye Laser Treatment on Infantile Hemangioma: Induction of Endothelial Apoptosis and Serum vascular endothelial growth factor (VEGF) Level Changes - Cao, Yongqian; Wang, Fagang; Jia, Qingwei; Xu, Rongjian; Dang, Wei; Chen, Qing; Lin, Li; Wang, Yibing (Journal of Lasers in Medical Sciences, 2014)
Introduction: Pulsed dye laser (PDL) is an important treatment for superficial infantile hemangioma, but few studies report on its cellular mechanism. The aim of this study was to evaluate alterations of serum vascular endothelial growth factor (VEGF) level in infantile hemangioma (IH) patients after laser treatment and effects of PDL irradiation on human umbilical vein endothelial cells (HUVECs) in vitro, as well as to explore the biomolecular mechanisms and ultrastructure changes of the PDL effect. Methods: 74 children with infant hemangioma including 45 patients in proliferating phase, 18 patients in involuting phase, 11 patients in involuted phase and 10 healthy children were engaged in this study. The plasma VEGF levels of children were measured with the enzyme-linked immunosorbent assay (ELISA). 24 hours after, HUVECs cultured in vitro were irradiated with PDL, cell apoptosis, mRNA levels of VEGF, and changes of ultrastructure were evaluated using flow cytometry, real-time reverse transcriptase polymerase chain reaction (RT-PCR), and transmission electron microscopy, respectively. Results: The serum VEGF concentrations in children with proliferating hemangiomas were significantly higher than in patients with involuting / involved hemangiomas and healthy patients. After receiving 3 laser treatments, the plasma VEGF levels of IH patients in proliferating hemangiomas decreased significantly. PDL irradiation could down-regulate VEGF mRNA expression of HUVECs, and increase cell apoptosis rate. Conclusion: The present study demonstrates that PDL irradiation imparts apoptosis induction effects on HUVECs in vitro. Furthermore, our results suggest that vascular endothelial growth factor may be of particular importance in pathophysiology and PDL treatment of hemangiomas, also serum VEGF levels may be used as an aid in the follow up of IH. This provides valuable evidence of the PDL effect on infantile hemangioma.